Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.29252/ieepj.1.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Exam Cheating Among the High School Students: Role of Personality Characteristics, Sensation-Seeking, Locus of Control and Exam Anxiety

Abstract: The research purpose is to evaluate the personality characteristics, sensation-seeking, a locus of control and exam anxiety as the predictors of exam cheating among the high school students in Ahvaz City. Hence, the research employed a correlation and predictive method. The sample comprised 79 students with cheating background and 78 students without cheating background in the high schools of Ahvaz City. The selection of the cheating group was done with the confirmation and agreement of at least three teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(7 reference statements)
0
1
0
1
Order By: Relevance
“…Current works have recommended focus on truthfulness as the largest defense against deceit in every sphere of academic world. Results inspire university instructors and institutional policymakers to pay much attention to this dispositional protector (Behroozi, Rafiee & Yakhchali, 2019).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Current works have recommended focus on truthfulness as the largest defense against deceit in every sphere of academic world. Results inspire university instructors and institutional policymakers to pay much attention to this dispositional protector (Behroozi, Rafiee & Yakhchali, 2019).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Iako se smatra se da će osobe sa visoko izraženom osobinom traženja senzacija bez straha ulaziti u testnu situaciju i neće je vidjeti kao prijeteću (Behroozi et al, 2019), traženje senzacija u ovom istraživanju nije bilo statistički značajno povezano sa testnom anksioznošću. Odsustvo ove negativne korelacije može djelimično biti objašnjeno karakteristikama samog uzorka: moguće je da, zbog veličine uzorka, efekat traženja senzacija nije mogao biti u potpunosti registrovan.…”
Section: Moderaciona Analizaunclassified
“…Furthermore, Tadesse & Getachew, (2010) stated that the consequence of academic dishonesty has been long-lasting in many occurrences and its impediment for growth is largely alarming. Cheating negatively impacts the educational factors and the students are the most affected by that; for example, students may come to the conclusion that those who cheat are more successful (Behroozi, Rafiee and Yakhchali, 2019). Earlier, Bretag (2013) observed that current research on academic integrity often focuses on impacts related to teaching and learning, particularly in institutions of higher education at the undergraduate level.…”
Section: Introductionmentioning
confidence: 99%